A comparative study of particle swarm optimization and genetic algorithm - M. Almufti, Saman; Yahya Zebari, Amar; Khalid Omer, Herman (Journal of Advanced Computer Science & Technology, 2019)
This paper provides an introduction and a comparison of two widely used evolutionary computation algorithms: Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) based on the previous studies and researches. It describes Genetic Algorithm basic functionalities including various steps such as selection, crossover, and mutation.Â Â